Influencing Factors of Pressure Ulcer in Critically Ill Patients - Li WANG; Qianting CAI; Ping CHEN (康复学报)
Objective:To explore the influencing factors of pressure ulcer in critically ill patients and to provide the evidence for the prevention of clinic pressure ulcer.Methods:A casecontrol study was applied to this research. Thirty critically ill patients with pressure ulcers were collected in our hospital as the case group, and 30 patients who were admitted to the hospital during the same period without severe pressure ulcers were selected as the control group, and their clinic characteristics data were collected from clinical records, laboratory tests and by simple questionnaires. Univariate and multivariate logistic regression analysis were applied to find out the influencing factors of pressure ulcer.Results:Compared to the control group, the age, fall score and proportion of urinary incontinence in the case group were higher, while the degree of high school education or above that, Q2H, Braden score and number of caregivers in the case group was lower. Univariate logistic regression showed that higher age (OR=1.055,95%CI: 1.015-1.097), urinary incontinence (OR=4.500,95%CI: 1.094-18.503), higher fall score (OR=3.201,95%CI: 1.769-5.792) were risk factors, while higher education level (OR=0.318,95%CI: 0.108-0.938), higher Braden score (OR=0.396,95%CI: 0.233-0.675), Q2H turning over (OR=0.222,95%CI: 0.054-0.914) and more caregivers (OR=0.058,95%CI: 0.008-0.424) were the protective factors for pressure ulcer. After adjustment for covariates in multivariate logistic regression, only Braden score (aOR=0.397,95%CI: 0.160-0.983) and fall score (aOR=3.019,95%CI: 1.281-7.114) were independent factors of pressure ulcer.Conclusion:The Braden score and fall score are closely related to pressure ulcer, which indicates that clinical workers should pay more attention to those critically ill patients with low Braden scores or high fall scores in future work.